The Potential of Honey as a Prebiotic Food to Re-engineer the Gut Microbiome Toward a Healthy State - Schell, Kathleen R.; Fernandes, Kenya E.; Shanahan, Erin; Wilson, Isabella; Blair, Shona E.; Carter, Dee A.; Cokcetin, Nural N. (Frontiers in Nutrition, 2022)
Honey has a long history of use for the treatment of digestive ailments. Certain honey types have well-established bioactive properties including antibacterial and anti-inflammatory activity. In addition, honey contains non-digestible carbohydrates in the form of oligosaccharides, and there is increasing evidence from in vitro, animal and pilot human studies that some honeys have prebiotic activity. Prebiotics are foods or compounds, such as non-digestible carbohydrates, that are used to promote specific, favourable changes in the composition and function of the gut microbiota. The gut microbiota plays a critical role in human health and well-being, with disturbances to the balance of these organisms linked to gut inflammation and the development and progression of numerous conditions such as colon cancer, irritable bowel syndrome, obesity, and mental health issues. Consequently, there is increasing interest in manipulating the gut microbiota to a more favourable balance as a way of improving health by dietary means. Current research suggests that certain honeys can reduce the presence of infection-causing bacteria in the gut including Salmonella, Escherichia coli and Clostridiodes difficile, while simultaneously stimulating the growth of potentially beneficial species such as Lactobacillus and Bifidobacteria. In this paper, we review the current and growing evidence that shows the prebiotic potential of honey to promote healthy gut function, regulate the microbial communities in the gut, and reduce infection and inflammation. We outline gaps in knowledge and explore the potential of honey as a viable option to promote or re-engineer a healthy gut microbiome.